Biomimetic Black Phosphorus Nanosheet-Based Drug Delivery System for Targeted Photothermal-Chemo Cancer Therapy - Cao, Jinxiu; Qi, Junyang; Lin, Xun; Xiong, Yue; He, Fumei; Deng, Wenbin; Liu, Gan (Frontiers in Bioengineering and Biotechnology, 2021)
As a biodegradable material, black phosphorus (BP) has been considered as an efficient agent for cancer photothermal therapy. However, its systemic delivery faces several hurdles, including rapid degradation in blood circulation, quick clearance by the immune system and low delivery sufficiency to the tumor site. Here, we developed a biomimetic nanoparticle platform for in vivo tumor-targeted delivery of BP nanosheets (BP NSs). Through a biomimetic strategy, BP NSs were utilized to coordinate with the active species of oxaliplatin, (1,2-diaminocyclohexane) platinum (II) (DACHPt) complexions, and the nanoparticles were further camouflaged with mesenchymal stem cells (MSCs) derived membranes. We showed that the incorporation of DACHPt not only decelerated the BP degradation but also enhanced the anti-tumor effect by combining the photothermal effect with chemotoxicity. Furthermore, MSC membrane coating increased the stability, dispersibility and tumor-targeting properties of BP/DACHPt, significantly improving antitumor efficacy. In short, our work not only provided a new strategy for in vivo tumor-targeted delivery of BP NSs but also obtained enhanced anti-tumor effect by combining photothermal therapy with chemotherapy.